South Sudan Economic Update, June 2021 : Pathways to Sustainable Food Security - World Bank (World Bank, Washington, DC, 2021)
The South Sudan economy is projected to contract by 4.1 percent in FY2020/21, with growth negatively affected by the impact of the COVID-19 pandemic, lower oil production, floods, and increased conflict intensity in parts of the country. With the economic decline in FY2020/21, living conditions have deteriorated, with some 8.3 million estimated to need humanitarian assistance in 2021, reflecting an increase of 800,000 in the absolute number of people in need from 2020. At the same time, crisis-level food insecurity persists despite increased agricultural production, with exceptionally high food prices constraining access to food for large segments of population. Consequently, it is estimated that more than half of the population (7.2 million people) are facing severe food insecurity (IPC Phase 3 and above) in the period from April to July 2021. However, the fiscal deficit is expected to narrow to about 2.7 percent of GDP, reflecting higher than projected oil and non-oil revenue and the impact of fiscal consolidation efforts. In addition, the current account deficit is expected to narrow to 7.1 percent of GDP in FY2020/21, from 7.9 percent in FY2019/20, reflecting lower financial transfers to Sudan and lower net outflows of oil-related investments. Beyond FY2020/21, the economy may benefit from higher investments in the oil sector, as well as recovery in the nonoil sectors. Consequently, the economy is expected to recover faster than earlier estimated, with projected growth rates of 2.6 percent in FY2021/22 and 3.0 in FY2022/23. However, this outlook is uncertain and is conditional on peace and stability, commitment to economic and public finance management reforms, improved budgeting and allocation of resources, and stabilization of smallholder agriculture.